Time management governs climate resilience and productivity in the coupled rice–wheat cropping systems of eastern India - McDonald, Andrew J.; Balwinder-Singh; Keil, Alwin; Srivastava, Amit; Craufurd, Peter; Kishore, Avinash; Kumar, Virender; Paudel, Gokul; Singh, Sudhanshu; Singh, A.K.; Sohane, R.K.; Malik, R.K. (Nature Publishing Group, 2022)
India will need to produce 30% more wheat by 2050, and these gains must principally come from intensification in eastern India where low productivity is common. Through a dense network of on-farm surveys for the rice–wheat system in this region, we show that contemporary wheat sowing dates have a central influence on achieved and attainable yields, superseding all other crop management, soil and varietal factors. We estimate that untapped wheat production potential will increase by 69% with achievable adjustments to wheat sowing dates without incurring undesirable trade-offs with rice productivity, irrigation requirements or profitability. Our findings also indicate that transformative gains in wheat yields are only possible in eastern India if rice and wheat are managed as a coupled system. Steps taken to ‘keep time’ through better management of the annual cropping calendar will pay dividends for food security, profitability and climate resilience now and as a foundation for adaptation to progressive climate change.